Methods in microbiology. Volume 29, Genetic methods for diverse prokaryotes - Smith, Margaret C. M.; Sockett, R. Elizabeth; ScienceDirect eBooks (London ; New York : Academic Press, 1999)
This new volume presents overviews of the very latest genetic approaches in a diverse range of prokaryotes. Divided into three sections, the topics include essential techniques for genetic analysis, case studies in which genetic methods in carefully chosen genera are described and approaches are used in the elucidation of specific phenomena. Key features * Up-to-date chapters on essential techniques for genetic analysis in diverse bacteria * The use of plasmids, phages and transposons and their applications to new organisms * Genetic methods in medically and industrially important bacteria such as Mycobacteria, Neisseria, Bacteroides, Clostridia, and spirochaetes * Analysis of virulence in Helicobacter and Erwina * Genetic methods in Archae * Photosynthesis and respiration in Paracoccus and Rhodobacter * Bacillus subtilis sporulation.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Prokaryotes; Microbiology; Microbiology; Prokaryotes; Electronic books